Liposomal Forms of Fluoroquinolones and Antifibrotics Decorated with Mannosylated Chitosan for Inhalation Drug Delivery - Irina Le-Deygen; Anastasia Safronova; Polina Mamaeva; Yana Khristidis; Ilya Kolmogorov; Anna Skuredina; Peter Timashev; Elena Kudryashova (MDPI AG, 2023)
The severe course of COVID-19 leads to the long-terming pulmonary diseases, such as bacterial pneumonia and post-COVID-19 pulmonary fibrosis. Thus, the essential task of biomedicine is a design of new effective drug formulations, including those for inhalation administration. In this work, we propose an approach to the creation of lipid-polymer delivery systems for fluoroquinolones and pirfenidone based on liposomes of various compositions decorated with mucoadhesive mannosylated chitosan. A generalizing study on the physicochemical patterns of the interactions of drugs with bilayers of various compositions was carried out, and the main binding sites were identified. The role of the polymer shell in the stabilization of vesicles and the delayed release of the contents has been demonstrated. For the liquid-polymer formulation of moxifloxacin, a prolonged accumulation of the drug in lung tissues was found after a single endotracheal administration to mice, significantly exceeding the control intravenous and endotracheal administration of the drug.